Neural correlates of music familiarity and likability in hospital noise masking: A functional near-infrared spectroscopy study - Deng, Qiyin; Deng, Zhangyan; Xu, Lin; Song, Yuxuan; Cai, Jun (The Journal of the Acoustical Society of America, 2024)
Subjective factors of music have been proven to significantly influence the effect of music masking, while the neural mechanism of music masking is unknown. This study aims to explore the neural mechanism by which music masking improves subjective perception of noise in the population. A total of 40 healthy subjects were recruited for both the subjective evaluation and functional near-infrared spectroscopy scanning during music masking of hospital noise. Annoyance reduction percentage (ARP), likability, familiarity, and brain response data were collected and analyzed. The results showed that the increasing of ARP and likability was significantly correlated with the activation of the bilateral dorsal-lateral superior frontal gyrus (DLPFC) and the orbital middle frontal gyrus (OFC), while the improvement of familiarity significantly activated the triangular inferior frontal gyrus, supramarginal gyrus, and middle temporal gyrus. The repeatedly activated channels located in DLPFC and OFC indicate that likability may play a key role in reducing annoyance through music masking. This study provides a scientific basis for the selection of masking music future noise management in hospitals.